Hedonic Broadband Prices Amid High Inflation and Market Consolidation: A Hungarian Case Study - Zoltán Pápai; Aliz McLean; Tamás Bukur (International Telecommunications Society (ITS), 2024)
This study examines the changes in consumer prices within the fixed broadband market in Hungary between 2020 and 2023, a period marked by unprecedented, government-backed market consolidation. Leveraging a hedonic price regression methodology, we inspect price changes in the context of internet service provider (ISP) differences, inflation, and various service features offered in broadband plans. The hedonic method allows for quality-adjusted price tracking over time, in addition to offering insights into the intrinsic value placed on various plan characteristics by consumers. We demonstrate that the hedonic methodology holds significant value for regulators and market players in developing effective price monitoring systems. Our analysis reveals that following the market consolidation, the previously stagnant price level increased, and the pricing strategies of the three major service providers underwent notable transformations. The two providers involved in the consolidation significantly raised their prices, with Vodafone becoming the most expensive provider in the country and Digi nearly losing its price advantage. By the end of the period, the third player, Telekom, offered more favourable hedonic prices compared to 2020. The cumulative increase in the average hedonic price index over the examined period was almost 20%, remaining significantly below the change in the consumer price index. The estimated intrinsic prices of the various fixed broadband plan characteristics are consistent with previous literature. The study underlines the utility of the hedonic methodology in providing nuanced insights into ISP pricing behaviour and fixed retail telecom market dynamics. The study opens up potential areas for future research, such as extending the analysis to television and voice telephony and monitoring future trends in light of the recent changes in market structure.
Keywords: 330; hedonic regression; telecommunications; fixed broadband; pricing; Hungary